Upper Airway Obstruction in a Newborn with Vallecular Cyst - Birgin Torer; Bilin Cetinkaya; Serkan Yılmaz; Cuneyt Yilmazer; Hande Gulcan (EL-Med-Pub, 2015)
Vallecular cyst is a rare cause of stridor in neonates, which may present as a life threatening airway obstruction. Here, we report a preterm infant with a congenital vallecular cyst who presented with stridor and respiratory distress that developed immediately after birth. She was successfully treated with endoscopic marsupialization.